دور القاضي الإداري الجزائري في حماية حقوق و حريات الموظف العام - - ضريف عادل; - حسيني أحمد بلال; - بسر البشير (University of Eloued جامعة الوادي, 2023)
يعد القضاء الإداري الجزائري إحدى أهم الضمانات التي تدافع عن حقوق وحريات الموظف العام، في مواجهة السلطة الإدارية وذلك من خلال القاضي الإداري، حيث يعتبر هذا الأخير هيئة فاصلة ومستقلة لفض النزاعات القائمة بين الموظف العام والإدارة، لذلك يلجأ الموظفون إليه قصد فض نزاعاتهم التي تأثر على حقوقهم،ومن اجل ذلك فقد أعطى المشرع للقاضي الإداري آليات رقابية عن طريق دعوى الإلغاء ودعوى التعويض، حيث تتمثل دعوى الإلغاء في طلب إلغاء قرار أو تصرف إداري صدر عن جهة إدارية والذي يعتبر غير قانوني،أو ينتهك القوانين واللوائح المعمول بها، يمكن للموظفين المتأثرين بهذا القرار أو التصرف المطعون فيه رفع دعوى أمام القضاء الإداري بإلغاء هذا القرار، في حين تتمثل دعوى التعويض في جبر الضرر الذي تكبده الموظف العام، نتيجة قرار أو تصرف إداري غير قانوني يمكنه رفع دعوى تعويض أمام القاضي الإداري، ومن خلال هذه الدعاوى يساهم القاضي الإداري في ضمان العدالة وحماية حقوق وحريات الموظف العام ، وكل هذا يهدف إلى إبراز أن جميع تصرفات وأعمال الإدارة خاضعة لمراقبة القاضي الإداري الذي يسهر على احترام الحقوق والحريات للموظف العام.Algeria's administrative judiciary is one of the most important guarantees that defend the rights and freedoms of the administrative officer. Public servants ", where the latter is considered to be an independent and decisive body for resolving disputes between public servants and management, Staff members therefore resort to the agents in order to resolve disputes affecting their rights. For that reason, the legislator gave the administrative judge control mechanisms through the annulment and compensation proceedings, The application for cancelation is a request for annulment of an administrative decision or action issued by an administrative authority which is considered illegal, or in violation of applicable laws and regulations. Staff members affected by this decision or the impugned conduct may sue the Administrative Court for annulment of this decision. Damages ", while the claim for compensation consists of reparation for the injury suffered by the public official. As a result of an unlawful administrative, decision or conduct, he can file a claim for compensation before the administrative judge, through these proceedings, the administrative judge contributes to ensuring justice and protecting the rights and freedoms of the public official, all this is aimed at highlighting that all the actions and actions of the administration under the control of the administrative judge who ensures respect for the rights and freedoms of the public official.
مذكرة ماستر
Keywords: الموظف العام - القاضي الإداري - القضاء الإداري - دعوى الإلغاء - دعوى التعويض - الحقوق والحريات - السلطة الإدارية; public employee - administrative judge - administrative judiciary - annulment lawsuit - compensation lawsuit - rights and freedoms - administrative authorityا